Answer :
Answer:
1) [tex]f^{-1}(x)=\frac{x+2}{123}[/tex]
2) [tex]f(0.02235)=0.75[/tex]
3) [tex]x=0.02235[/tex]
Explanation:
Part 1)
Given that
[tex]f(x)=123x-2[/tex]
To find [tex]f^{-1}(x)[/tex] we put [tex]x=f^{-1}(x)[/tex] in the given function to obtain
[tex]f(f^{-1}(x))=123\times f^{-1}(x)-2\\\\\Rightarrow x=123\times f^{-1}(x)-2(\because f(f^{-1}(x)=x)\\\\\therefore f^{-1}(x)=\frac{x+2}{123}[/tex]
Part 2 and 3)
for [tex]f(x)=0.75[/tex] we put f(x) = 0.75 and then solve for 'x'
[tex]0.75=123\times x -2\\\\\therefore x=\frac{0.75+2}{123}=0.02235[/tex]